Identifikasi Ektoparasit Pada Ikan Lele Dumbo (Clarias gariepinus) Yang Di Budidayakan di Kolam Beton - Welnando, Rydho; Maryani, Maryani; Tantulo, Uras; Rozik, Mohamad (Jurnal Akuakultur Sungai dan Danau, 2024)
There are several obstacles for dumbo catfish farmers that result in losses, one of which is disease.  Diseases caused by parasitic infections can cause irritation to external organs such as gills and skin. This can cause disruption of respiration and osmoregulation processes and reduce fish immunity.   The population of ectoparasites in fish in the aquatic environment can be monitored through the identification of parasites by calculating their prevalence and intensity.  This study aims to identify ectoparasites, analyze the prevalence rate, intensity of ectoparasite attacks that attack dumbo catfish.  Sampling for 5 times in one week for 20 working days with the number of samples to be obtained as much as the catch of 3 stations.  Ectoparasites found in dumbo catfish are Dactylogyrus sp, Trichodina sp, Chilodonella sp, and Oodinium sp. The highest prevalence value was found in Dactylogyrus sp at station III with a percentage of 100% with a very frequent infection category. The highest intensity value was Trichodina sp. at station II which was 24.4 individuals/head with moderate category. The dominating ectoparasite was Dactylogyrus sp. The number of infected dumbo catfish was 30 out of 30 samples tested.  In Dactylogyrus sp there were a total of 258 parasites, followed by Chilodonella sp with a total of 69 parasites from 30 samples, Oodinium sp had a total of 47 parasites and Trichodina sp had a total of 151 parasites from 30 samples.  Water quality parameters measured during the study showed good values for the growth of dumbo catfish in the rearing ponds.